Process Reforms for a People-centred City: Ease of Living in Dibrugarh, Assam - Sudarshan Ozah; Partha Pratim Borah (Indian Journal of Public Administration, 2026)
This article examines issues of the ease of living emanating from the current urban scenario of Dibrugarh in Assam. Based on primary data collected through fieldwork, this study contextualises local lived experiences within the national framework. This research argues that Dibrugarh city’s urbanisation has outpaced institutional capacity and development due to administrative advancement, economic growth and population migration, generating drastic insufficiency of infrastructural development, social sustainability, efficient governance mechanisms and social assistance. The research highlights some major empirical results, including persistent shortcomings in municipal solid waste management and handling of waste collection systems, along with issues like intensified environmental concerns from river erosion, poor air quality owing to pollution, uneven access to basic services in slum areas and disintegrated governance with low citizen participation. The major argument of the work is that a multi-stakeholder approach is crucial for transforming infrastructure investments for long-term improvements in quality of life and ease of living in Dibrugarh city. To establish Dibrugarh city’s environment as more sustainable, resilient and inclusive, the government stakeholders and citizens must work collaboratively to find practical solutions, including integrated planning, improved solid waste management, sanitation, proper water supply systems, community engagement and targeted social and health initiatives, which will contribute to the ease of living in Dibrugarh.